Incretin-Based Therapies, Glucometabolic Health and Endovascular Inflammation - Rizzo, Manfredi; Nikolic, Dragana; Banach, Maciej; Maria Patti, Angelo; Montalto, Giuseppe; A. Rizvi, Ali (Current Pharmaceutical Design, 2014)
Incretin peptides are a group of gastrointestinal hormones that play a prominent role in the regulation of glucose metabolism. Incretin-based therapies (IBTs) have recently emerged as an important treatment option for patients with type 2 diabetes mellitus (T2DM). These pharmaceutical agents may be specially well suited for patients who are overweight or obese with primarily post-meal glucose peaks, and in whom traditional first-line oral agents have failed to maintain adequate glycemic control. There are 2 classes of IBTs: the dipeptidyl peptidase-4 (DPP-4) inhibitors and the glucagon-like peptide 1 (GLP-1) receptor agonists. The ultimate effect of both types of agents is to augment GLP-1 signaling, which results in enhanced glucose-dependent insulin secretion, inhibition of glucagon secretion and decreased appetite. This leads to improved regulation of glucose homeostasis accompanied by either no increase in body weight (with DPP-4 inhibitors) or a reduction (with GLP-1 receptor agonists). GLP-1 inhibits food intake and the increased GLP-1 response may contribute as a satiety signal. Although data regarding the effect of GLP-1 agonists and DPP-4 inhibitors on levels of peptides involved in the regulation of food intake in T2DM are few, an indirect effect of IBT on weight loss is possible (e.g. Exendin-4 induces adiponectin secretion in vitro). Results from animal models indicate reduction of food intake and body weight by GLP-1 agonists, but follow-up studies are required. A growing amount of evidence suggests that these peptides may also impact the cardiovascular system, including beneficial effects on myocardial cells, lipid profiles and blood pressure as well as reduced markers of systemic inflammation and improved endothelial dysfunction. The potential role of these agents in improving components of the metabolic syndrome and retardation of atherosclerosis needs to be fully elucidated. Although IBTs are currently recommended only for use in the early treatment of T2DM, the ‘non-glycemic’ actions of these drugs may have far reaching therapeutic implications. It is hoped that future studies will elucidate their potential strengths and weaknesses for use in various metabolic conditions.
Keywords: type 2 diabetes mellitus